Antioxidant Activity of Endophytic Fungus Phyllosticta sp. Isolated from Guazuma tomentosa - R. Shenbhagaraman; J. Muthumary, K. Srinivasan*, L.K. Jagadish (Journal of Phytology, 2010)
SUMMARY Antioxidant property of Phyllosticta sp. culture filtrate extracted with ethanol was evaluated in vitro. ABTS and DPPH radicals were used to evaluate their antioxidant activity. Antioxidant components like total phenol and flavonoid were also determined. The ethanolic extract of Phyllosticta sp. showed potent antioxidant activity against both ABTS and DPPH radicals with the EC50 value of 580.02 ± 0.57µg/ml and 2030.25±0.81 µg/ml respectively. Total amount of phenol and flavonoid quantified were of 18.33 ± 0.68 gallic acid equivalents per gram and 6.44 ± 1.24 µg/mg of quercetin equivalent respectively. In conclusion, the culture filtrate of Phyllosticta sp. may have potential source of natural antioxidant. Key words: Antioxidant, ABTS, DPPH, phenol, Phyllosticta sp. <span style="font-weight: normal; font-size: 7pt; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">K. Srinivasan et al. Antioxidant Activity of Endophytic Fungus Phyllosticta sp. isolated from Guazuma tomentosa. J Phytol 2/6 (2010) 37-41.